Antidiarrheal and Cardio-Depressant Effects of Himalaiella heteromalla (D.Don) Raab-Straube: In Vitro, In Vivo, and In Silico Studies - Fatima Saqib; Faisal Usman; Shehneela Malik; Naheed Bano; Najm Ur-Rahman; Muhammad Riaz; Romina Alina Marc (Vlaic); Crina Carmen Mureşan (Plants, 2021)
Himalaiella heteromalla (D.Don) Raab-Straube is a commonly used remedy against various diseases. Crude extract and fractions of H. heteromalla were investigated for a gastrointestinal, bronchodilator, cardiovascular, and anti-inflammatory activities. H. heteromalla crude extract (Hh.Cr) relaxed spontaneous contractions and K+ (80 mM)-induced contraction in jejunum tissue dose-dependently. The relaxation of K+ (80 mM) indicates the presence of Ca++ channel blocking (CCB) effect, which was further confirmed by constructing calcium response curves (CRCs) as they caused rightward parallel shift of CRCs in a manner comparable to verapamil, so the spasmolytic effect of Hh.Cr was due to its CCB activity. Application of Hh.Cr on CCh (1 µM) and K+ (80 mM)-induced contraction in tracheal preparation resulted in complete relaxation, showing its bronchodilator effect mediated through Ca++ channels and cholinergic antagonist activity. Application of Hh.Cr on aortic preparations exhibited vasorelaxant activity through angiotensin and α-adrenergic receptors blockage. It also showed the cardio suppressant effect with negative chronotropic and inotropic response in paired atrium preparation. Similar effects were observed in in vivo models, i.e., decreased propulsive movement, wet feces, and inhibition of edema formation.